Fashion and history an virtual environment, the challenge and proposes (ModaPalavra e-periódico, 2011)
Report and discussion of the proposal of a virtual environment composition for the results diffusion obtained in the research project "Brazil for its appearances," taking into account the study on other virtual environments developed for historical themes, the Fashion student profile and their needs for information on Brazil´s fashion history.
Keywords: Virtual environments; distance education; history of fashion